RETRACTED: Assessing the prospects of distributed ledger technology (DLT) development as an element of digital ecosystem of railway transport - Lyakina M.A.; Fedorov A.E. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001